Caelius Aurelianus‘ textbook on medicine of the fifth century: rhythm in asthma, pain, and drug effects - Lemmer, Björn (Chronobiology international, 2019)
Caelius Aurelianus was a Greek-Roman physician in the fifth century. He translated the work of Soranus from Ephesus into Latin and extended the medical knowledge of his time in several textbooks. His book “De Morbis acutis et chronicis” was reprinted many times up to the 19th century and served as the handbook for physicians. Aurelianus aready described in detail the rhythmic pattern - daily and seasonally - of asthma. Tooth pain was also first described by Caelius Aurelianus to peak at night and that drugs were not able to fully suppress the pain, a first indication of chronopharmacology.
Gesehen am 04.12.2019